Synthesis and Characterization of Some Derivatives of 4,5-Dimethyl-Δ4-N-aryl-N-ethylimidazoline-2-thione - Belboukhari, N.; Cheriti, A.; Djafri, A.; Roussel, C. (Asian Journal of Chemistry, 2010)
The azoline compounds which are the derivatives of imidazole possess many applications such as raw materials in the industrial chemistry, in polymers and pharmaceutical chemistry. A large number of natural products containing in nitrogenous heterocyclic compounds have some biological properties. The nucleic acids (ADN, ARN) which are responsible for genetic heritage and essential element of cellular core, are formed of basis of imidazoline (e.g., guanine, adenine and cytosine). In pursuiance of present research works on the set of the azolines, we intend to synthesize some derivatives of N-aryl imidazole (d) through condensation between the thiourea (c) derivatives and the acetone by refluxation in pyridine. The synthesized azolines have been characterized by infrared, UV and NMR.